PERAN BELANJA MODAL PEMERINTAH DAN INVESTASI PEMBANGUNAN MANUSIA DALAM MENGURANGI TINGKAT KEMISKINAN DI INDONESIA - Khodijah Mustaqimah; Sri Hartoyo; Idqan Fahmi (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2017)
Poverty is a measure of socio-economic conditions in assessing the success of development undertaken by a government in a region. There are many negative impacts resulted from poverty, among others, social and economic problems. People who live in poverty usually suffer from malnutrition, poor health, high illiteracy rates, are in poor environment and in lack of access to infrastructure and adequate public services. The purpose of this study was to analyze the impact of human development and government capital expenditure on reducing poverty in Indonesia. The model was estimated by using 2SLS method. Several simulations was also conducted to look at the impact of the allocations of government expenditure on health, education and government capital expenditure on reducing poverty. The results showed that government capital expenditure and human development have significant impacts on reducing poverty in Indonesia with government expenditure on education gives the greatest impact. Keywords: Capital, Expenditure, Government, Human Development, Poverty